医学科技论文中常见统计学问题分析 及建议. - 王雅洁; 李亚琴 (Chinese Nursing Research, 2021)
This paper analyzed common statistical problems in medical scientific papers and during process of papers revision and papers edition. It put forward possible ways and suggestions to avoid statistical error, which was convenient for researchers to learn when writing papers, and also provide references for medical journal editors to deal with similar papers.